In ovo Administration of Defined Lactic Acid Bacteria Previously Isolated From Adult Hens Induced Variations in the Cecae Microbiota Structure and Enterobacteriaceae Colonization on a Virulent Escherichia coli Horizontal Infection Model in Broiler Chickens - Arreguin-Nava, Margarita A.; Graham, Brittany D.; Adhikari, Bishnu; Agnello, Melissa; Selby, Callie M.; Hernandez-Velasco, Xochitl; Vuong, Christine N.; Solis-Cruz, Bruno; Hernandez-Patlan, Daniel; Latorre, Juan D.; Tellez, Guillermo; Hargis, Billy M.; et al. (Frontiers in Veterinary Science, 2020)
The effects of in ovo administration of a defined lactic acid microbiota (LAM), previously isolated from adult hens, in the cecae microbiota structure and Enterobacteriaceae colonization after exposure to virulent Escherichia coli during the hatching phase of broiler chickens were evaluated. Embryos inoculated with LAM showed a significant (P < 0.05) reduction of Enterobacteriaceae colonization at day-of-hatch (DOH) and day (d) 7. Furthermore, there was a significant increase in total lactic acid bacteria on DOH, body weight (BW) DOH, BW d7, and d0–d7 BW gain and reduced mortality d0–d7 was observed in the LAM group compared with that in phosphate-buffered saline (PBS) control. The bacterial composition at the family level revealed that the Enterobacteriaceae was numerically reduced, whereas the Ruminococcaceae was significantly increased in the LAM group when compared with that in the PBS control. Moreover, the bacterial genera Proteus and Butyricicoccus and unidentified bacterial genera of family Lachnospiraceae and Erysipelotrichaceae were significantly enriched in the LAM group. In contrast, the Clostridium of the family Peptostreptococcaceae and unidentified genus of family Enterobacteriaceae were significantly abundant in the PBS control group. In summary, in ovo administration of a defined LAM isolated from adult hens did not affect hatchability, improved body weight gain and reduced mortality at d7, induced variations in the cecae microbiota structure and reduced Enterobacteriaceae colonization on a virulent E. coli horizontal infection model in broiler chickens.